2015
DOI: 10.1007/978-3-319-16024-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Spatial Interpolation Methods for Mapping Meteorological Data in Turkey

Abstract: Determining the potentials of the renewable energy sources provides realistic assumptions on useful utilization of the energy. Wind speed and solar radiation are the main meteorological data used in order to estimate renewable energy potential. Stated data is considered as point source data since it is collected at meteorological stations. However, meteorological data can only be significant when it is represented by surfaces. Spatial interpolation methods help to convert point source data into raster surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Site 29, situated far from the other sites, was excluded from this analysis. Wind speed was estimated using the inverse weighted distance interpolation method (Keskin et al 2015 ). Temperature and RH layers were developed employing a linear regression model using residual-corrected altitude as the independent, explanatory variable.…”
Section: Methodsmentioning
confidence: 99%
“…Site 29, situated far from the other sites, was excluded from this analysis. Wind speed was estimated using the inverse weighted distance interpolation method (Keskin et al 2015 ). Temperature and RH layers were developed employing a linear regression model using residual-corrected altitude as the independent, explanatory variable.…”
Section: Methodsmentioning
confidence: 99%
“…For keeping this method simple and fast and also because grid points are not very close with a distance of about 50 km, only four neighbouring points were considered for interpolation. Inverse Distance Weighting is a commonly used method in meteorology [26], which in several cases has been proved to be the best method for interpolation among others [28] [29], such as Kriging. As Bicubic Interpolation delivered negative wind speeds in some cases it was discarded for further use.…”
Section: Simulation Of Wind Power Generationmentioning
confidence: 99%
“…Comparative studies between the application of semivariance and inverse interpolation of distance power are compromised because most of the researchers use the power of 2, although they are not ideal for such variables studied. One example is the study done by Luo et al (2008) and Keskin et al (2015) which reported that the IPD result was inadequate and attributed it to the weight at points where it is influenced by neighboring points, being this value weight 2 for the study of wind spatialization. These data obtained for the wind velocity are an indispensable application for the estimation of the average velocities and bursts of the wind in regions of agricultural interest, contributing to the calculation of the more accurate ETo (Allen et al, 1998).…”
Section: Estimated Power Value Performancementioning
confidence: 99%